The Secrets of Meristems Initiation: Axillary Meristem Initiation and Floral Meristem Initiation - Qingqing Yang; Cunquan Yuan; Tianci Cong; Qixiang Zhang (Plants, 2023)
The branching phenotype is an extremely important agronomic trait of plants, especially for horticultural crops. It is not only an important yield character of fruit trees, but also an exquisite ornamental trait of landscape trees and flowers. The branching characteristics of plants are determined by the periodic initiation and later development of meristems, especially the axillary meristem (AM) in the vegetative stage and the floral meristem (FM) in the reproductive stage, which jointly determine the above-ground plant architecture. The regulation of meristem initiation has made great progress in model plants in recent years. Meristem initiation is comprehensively regulated by a complex regulatory network composed of plant hormones and transcription factors. However, as it is an important trait, studies on meristem initiation in horticultural plants are very limited, and the mechanism of meristem initiation regulation in horticultural plants is largely unknown. This review summarizes recent research advances in axillary meristem regulation and mainly reviews the regulatory networks and mechanisms of AM and FM initiation regulated by transcription factors and hormones. Finally, considering the existing problems in meristem initiation studies and the need for branching trait improvement in horticulture plants, we prospect future studies to accelerate the genetic improvement of the branching trait in horticulture plants.